2020
DOI: 10.1111/ina.12726
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the intelligibility of irrelevant speech and cognitive performance—A revised model based on laboratory studies

Abstract: Dissatisfaction with acoustic conditions is a common problem in open-plan offices, as documented by numerous researchers over several decades. 1-6 Similar problems are also encountered nowadays in activity-based offices, albeit to a lesser extent. 7-9 Of the different noise sources in open-plan offices, speech is the main source of noise annoyance, 3,5,10 correlating highly with the general perception of disturbing noise. 11 The acoustic problems are not restricted to subjective discomfort but have more direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 67 publications
(248 reference statements)
0
14
0
Order By: Relevance
“…Office noise and lack of speech privacy are among the environmental factors causing the largest dissatisfaction in open-plan offices [1]. One of the main reasons for this might be that work performance in concentration-demanding tasks has been found to improve with reducing intelligibility of irrelevant speech [2]. This is supported by the finding that disturbance due to noise was lower in offices having lower speech intelligibility [3].…”
Section: Introductionmentioning
confidence: 96%
“…Office noise and lack of speech privacy are among the environmental factors causing the largest dissatisfaction in open-plan offices [1]. One of the main reasons for this might be that work performance in concentration-demanding tasks has been found to improve with reducing intelligibility of irrelevant speech [2]. This is supported by the finding that disturbance due to noise was lower in offices having lower speech intelligibility [3].…”
Section: Introductionmentioning
confidence: 96%
“…To control the problems caused by speech and avoid the ISE, the STI (0 = not intelligible, 1 = perfectly intelligible) must be reduced at least below a value of 0.5 or even lower. Recent studies have shown that the decrease in cognitive performance begins above STI = 0.21 (Haapakangas, Hongisto, and Liebl 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A higher sound pressure level may be associated with a higher psychological demand for natural features ( Pheasant et al, 2008 ; Annu et al, 2020 ). The requirement for acoustic environments would also be higher for complex tasks (e.g., English reading comprehension) than simple tasks ( Haapakangas et al, 2020 ; Lou and Ou, 2020 ). However, comparative studies remain narrow in focus dealing only with accuracy rates and subjective perceptions.…”
Section: Introductionmentioning
confidence: 99%